Artificial Intelligence in Healthcare CRM: A Systematic Review of Emerging Technologies and Patient-Centered Applications - Jaymin Harishkumar Sutarwala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating Artificial Intelligence (AI) in Healthcare Customer Relationship Management (CRM) systems represents a significant advancement in modern healthcare delivery. This comprehensive review examines emerging innovations at the intersection of AI and Healthcare CRM, focusing on machine learning algorithms, predictive analytics, and natural language processing applications. The research demonstrates how these technologies enhance patient care through improved risk prediction, personalized treatment planning, and automated communication systems. Further investigation explores the implementation of AI-powered solutions for sentiment analysis and patient feedback interpretation, leading to enhanced service delivery and patient retention. The study addresses critical challenges in data privacy, ethical considerations, and cybersecurity measures necessary for protecting sensitive patient information. The findings indicate that while AI integration in Healthcare CRM systems demonstrates substantial potential for improving operational efficiency and patient outcomes, successful implementation requires careful consideration of regulatory compliance and ethical guidelines. This research contributes to the growing body of knowledge on healthcare digitalization by providing insights into the transformative potential of AI in patient relationship management and identifying key areas for future research and development. The work concludes with recommendations for healthcare providers and technology developers to optimize the integration of AI in Healthcare CRM systems while maintaining high standards of patient care and data security.